2021
DOI: 10.3389/fimmu.2021.633436
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Dendritic Cells, T Cell Tolerance, and Dendritic Cell Therapy for Immunologic Disease

Abstract: Dendritic cells (DC) are antigen-presenting cells that can communicate with T cells both directly and indirectly, regulating our adaptive immune responses against environmental and self-antigens. Under some microenvironmental conditions DC develop into anti-inflammatory cells which can induce immunologic tolerance. A substantial body of literature has confirmed that in such settings regulatory DC (DCreg) induce T cell tolerance by suppression of effector T cells as well as by induction of regulatory T cells (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 214 publications
(265 reference statements)
1
44
0
1
Order By: Relevance
“…The use of 1,25-dihydroxyvitamin D3, calcitriol, the active form of VD3, is one of the most widely established protocols for the generation of tolerogenic DCs ( 36 , 68 ). VD3 activates intracellular metabolic pathways in DCs via the PI3K/Akt/mTOR pathway that regulates glycolysis, retaining DCs in a more immature state with reduced expressions of CD80/86 and HLA-DR ( 36 , 69 , 70 ).…”
Section: Tolerogenic Adjuvants: Effects On Dcs and Neutrophilsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of 1,25-dihydroxyvitamin D3, calcitriol, the active form of VD3, is one of the most widely established protocols for the generation of tolerogenic DCs ( 36 , 68 ). VD3 activates intracellular metabolic pathways in DCs via the PI3K/Akt/mTOR pathway that regulates glycolysis, retaining DCs in a more immature state with reduced expressions of CD80/86 and HLA-DR ( 36 , 69 , 70 ).…”
Section: Tolerogenic Adjuvants: Effects On Dcs and Neutrophilsmentioning
confidence: 99%
“…Other well-recognized tolerogenic adjuvants are CS, which exert immunosuppressive effects via NFκB inhibition ( 36 , 68 , 76 ). Dexamethasone (Dex) is a commonly used synthetic CS.…”
Section: Tolerogenic Adjuvants: Effects On Dcs and Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Injection of dendritic cells tolerized for LDL by pre-incubation with apoB100 and IL-10 was found to reduce atherosclerosis by 70% in ldlr − /− mice with a transgenic expression of human apoB100 [121]. Moreover, early clinical trials have indicated positive effects of tolerogenic dendritic cell therapy in rheumatoid arthritis and Crohn's disease [126].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In allergic reactions, the use of naturally-occurring or induced tolerogenic dendritic cells (tDCs) may be a prophylactic and therapeutic option to control exacerbated immune responses [17]. The techniques of isolation and reprogramming of DCs toward tolerogenic profiles are well characterized, the latter including treatment with some cytokines such as transforming growth factor (TGF)-β, interleukin (IL)-10, and/or pharmacological agents such as corticosteroids or rapamycin [18]. There are studies showing that bone marrow-derived DCs exposed in vitro to IL-10 and transferred to ovalbumin (OVA)-induced allergic mice reduced airway hyperresponsiveness, eosinophilia, and Th2 cytokine release [19].…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%